2014
DOI: 10.3109/02770903.2014.939282
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of asthma by occupation: Washington State Behavioral Risk Factor Surveillance System Data, 2006–2009

Abstract: ObjectiveObjective: To estimate the prevalence of asthma in workers by occupation in Washington State. Methods: Data from the 2006–2009 Behavioral Risk Factor Surveillance System (BRFSS) and the BRFSS Asthma Call-Back Survey (ACBS) in Washington State (WA) were analyzed. Using state-added and coded Industry and Occupation questions, we calculated prevalence ratios (PRs) for 19 occupational groups. Results: Of the 41 935 respondents who were currently employed during 2006–2009, the prevalence of current asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Michigan data also showed that education had the second highest prevalence of current asthma, although it was not significantly larger than the prevalence among all workers combined. By using 2006–2009 BRFSS data from the State of Washington, Anderson et al ( 3 ) found that 3 occupational groups — teachers (all levels), and counselors; administrative support workers, including clerical workers; and health service workers — had significantly higher prevalence ratios of current asthma than prevalence in all industries ( 3 ). Because of sample size limitations, we were unable to conduct analyses by the occupation subcategories used in Washington.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Michigan data also showed that education had the second highest prevalence of current asthma, although it was not significantly larger than the prevalence among all workers combined. By using 2006–2009 BRFSS data from the State of Washington, Anderson et al ( 3 ) found that 3 occupational groups — teachers (all levels), and counselors; administrative support workers, including clerical workers; and health service workers — had significantly higher prevalence ratios of current asthma than prevalence in all industries ( 3 ). Because of sample size limitations, we were unable to conduct analyses by the occupation subcategories used in Washington.…”
Section: Discussionmentioning
confidence: 99%
“…None of our combined occupation categories had elevated prevalence of asthma after controlling for covariates. Neither of 2 previously published analyses of asthma analyses controlled for covariates ( 3 , 4 ). Results from the 21-state study and Michigan and Washington suggest industries and occupations that should be targeted for health education efforts regarding asthma management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of occupational asthma cases have been reported in the last years linked to pollution of the air in different workplaces, in parallel with the increase of the number of people employed in service activities and with a better risk control of the industrial environment. (14,15) There are more than 350 substances with asthmogenic risk in workplaces. (16) Reduction of their utilization and of their concentration in the air diminishes the risk of asthma development and also the risk of aggravation of a pre-existing asthma, significantly improving the quality of life for these patients.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Internationally, a study of more than 41,000 workers in 19 broad occupational groups in the US reported a prevalence of OA of 8.1% (95% CI 7.8–8.5%). When compared to a reference group of administration workers, the highest prevalence ratios (PR) were reported for health workers (PR 1.5, 95% CI 1.2–1.9) and teachers (PR 1.3, 95% CI 1.1–1.6) 4 …”
mentioning
confidence: 94%